Gripping Boundaries: Animal Style Contingencies in c.AD 600–800 Scandinavia - Skare, Mats (Danish Journal of Archaeology, 2025)
This article examines the role of Scandinavian animal styles in the early Viking Age. It first assesses several strands of relevant discourse in the research history. One line of argument suggests a link between early and late animal styles. That postulate serves as the article’s next point of departure. By focusing on the timespan of c.AD 600–800, the connection between ‘Gripping Beast Style’, Style III/E, Style 2.5/D, and Style II is sought. Building on pioneering formulations, the styles’ respective definitions are amended. The styles’ iconographic contents are then explored through their respective archaeological-historical backdrops. Ontological models serve as the analysis’ next consideration. It is argued that the material mainly reveals animistic and/or totemistic worldly understandings. Accordingly, the active use of, and shifts in, Scandinavian animal styles, may be related to an increasing politico-religious divide between the Nordic sphere and the rest of the continent. This could constitute one of many facets ‘vikings’ applied in their alienation of others, thereby justifying extreme violence.